Basic Health Care: a comparison between prenatal care in the Family Health Unit and in traditional services (Brazilian Journal of Health Research, 2022)
Introduction: The Family Health Strategy (FHS) program is a gateway to health services, such as prenatal care in Primary Care, which helps preventing, early identifying and treating undesirable events during pregnancy, at childbirth and to newborns. Objectives: Comparing socioeconomic, demographic, obstetric and prenatal care features between pregnant women followed-up in the Family Health Strategy (FHS) and those treated in other public health services in São Luís City - MA. Methods: Descriptive study based on data deriving from BRISA cohort, conducted with probabilistic sample comprising 4,250 women; analyses were performed through chi-square test. Results: in total, 38.2% of the investigated women were assisted by the FHS; they differed from each other as to age and professional occupation of the head of the family. Women treated by FHS were the ones who attended more than at least 4 to 6 nursing consultations (p
Keywords: Pregnant women; Prenatal care; Family Health Strategy; Maternal Health Services; Unified Health System